Popular heritage in Damascus during the twentieth century Hammams as a model: تعرف الحمام لغة واصطلاحاً -أنواع الحمامات -مناسبات ارتياد الحمامات - المعتقدات الشعبيّة والحمامات في دمشق -: أشهر حمامات دمشق (Journal of Hama University, 2026)
The Damascene cultural heritage represents an artistic and cultural wealth that, until recently, was subject to extinction and random waste. Due to its importance, several institutions were established to protect, maintain, rehabilitate and display it in a manner that lives up to its historical, archaeological and social value. The city of Damascus is proud of its ancient history and intellectual and urban heritage. It has been an eternal presence since the fourth millennium BC, and a growing city despite the various circumstances it has gone through.Damascus is one of the world's tourist centers, as God has blessed it with natural beauty, abundant water and orchards, and its location in a very fertile plain. In Ghouta, it is considered one of the best paradises in the world. Damascus is also distinguished by the simplicity of its buildings from the outside, the diversity of its decorations and antiquity from the inside, and the kindness of its residents and their skill in managing their affairs. Many of its buildings became famous, including the house of Abdullah Bey al-Azm at the northern end of the Buzuriyah market, and the house of Youssef Effendi Anbar in al-Hariqa, in addition to many buildings whose traces still remain to this day.Damascus was famous for its markets distributed among its neighborhoods, such as Al-Daqaqin, Al-Buzuriyah, Al-Habbalin, Al-Jaqmaq, Al-Asrouniyyah, Al-Qoton, Al-Khail, Al-Jamal, Al-Khudroiyah, Al-Manakhiliyah, Al-Soof, and others. Its visitors agreed on the mastery, order, elegance, and cleanliness of its baths, such as Al-Khayyatin, Al-Qishani, Al-Nawfarah, Nour Al-Din Al-Shaheed, Sharkas, and other baths located between the markets and neighborhoods, which were helped by the flow of water from every direction. The baths were an important phenomenon of the Damascene cultural heritage through what they gathered within their walls of popular social customs and traditions that Damascene society knew and maintained for several centuries. With the passage of time, the economic and social changes in Damascene society contributed to changing this behavior and changing its concepts between the past and the present, as the number of baths decreased and the number of their visitors decreased, especially during the second half of the twentieth century, and visits to them were limited to tourist groups and some interested and lovers of authenticity and old customs.
Keywords: : Bath, Damascus, popular, customs, traditions, weddings, outside, middle, inside